Effects of SiO2/CaO ratio on viscosity, structure, and mechanical properties of blast furnace slag glass ceramics - Jia, Ruidong; Deng, Leibo; Yun, Fei; Li, Hao; Zhang, Xuefeng; Jia, Xiaolin (Materials chemistry and physics, 2019)
In an attempt to improve the effective utilization of solid waste generated in the steel industry and reduce the production cost of glass ceramics, glass ceramics were prepared from blast furnace slag as the main raw material. The effects of SiO2/CaO molar ratio on the viscosity, structure, and properties of the as-prepared CaO–MgO–Al2O3–SiO2 (CMAS) blast furnace slag glass ceramics were investigated by viscometry, X-ray diffraction, scanning electron microscopy, Raman spectroscopy, and physicochemical property measurements. The results showed that with decreasing SiO2/CaO ratio, the viscosity and degree of polymerization of molten glass significantly decreased, and the main crystalline phase transformed from single diopside to a combination of augite and gehlenite phases, which affected the physicochemical properties of the glass ceramics. The glass ceramic sample with a density of 2.78 g/cm3 exhibited the best comprehensive performance: bending strength of 182.86 MPa, microhardness of 7.34 GPa, acid resistance of 95.21%, and alkali resistance of 98.43%. The various characterization results proved that the prepared glass ceramics could be potentially used for several industrial applications. •Glass-ceramics was prepared from blast furnace slag as main raw material.•The decrease in SiO2/CaO ratio caused significant decrease in the viscosity and extent of polymerization of glass melts.•The main crystalline of glass-ceramics transformed from diopside to the concomitant phases of augite and gehlenite.